Development of Higher Order Thinking Skills (HOTS) Test Instruments in Geometry - Octaria, Dina; Ningsih, Yunika Lestaria; Destiniar, Destiniar; Fitriasari, Putri (JTAM (Jurnal Teori dan Aplikasi Matematika), 2022)
Critical thinking, creativity, communication, and collaboration are all skills that students must have in the twenty-first century. A meaningful assessment, where the assessment can develop higher-order thinking skills, is one effort to realize the achievement of 21st-century skills. The goal of this research is to develop a HOTS test instrument relying on valid and reliable geometry for students. This study is a development study that employs the Akker development model. This study's data was gathered through questionnaires, documentation, interviews, and tests. The data were descriptively, qualitatively, and quantitatively analyzed. As a result of this research, the HOTS test instrument on the developed material is valid and reliable for students. The results of the expert's assessment of the content and language of the questions indicate the validity of the questions. The overall validity of the test instrument is 85.71 percent. A large-scale trial involving 110 students in grade 10 of senior high school yielded the empirical validity and reliability of the test items, with the test results indicating that 18 items were declared valid and reliable. As a result, the created Geometry test instrument can be used to assess students' HOTS abilities.